Analysis of Preparation for Implementation of Posyandu Toddlers in New Normal Condition - Syahrum; Deharnita; Gafar (POLTEKKES KEMENKES PADANG, 2023)
With the Covid-19 outbreak hitting many countries in the world, including Indonesia, it has an impact on the implementation of posyandu , Posyandu is a form of social life in the community which is one form of community-sourced effort. The purpose of the study was to obtain a description of the behavior of mothers of children under five in preparing for the implementation of posyandu in new normal conditions.The qualitative research design aims to obtain an overview of the preparation for the implementation of posyandu in new normal conditions in Solok City. The research was carried out in Solok City in 2021. Data were collected using in-depth interviews with informants of mothers of toddlers, cadres, people in charge of posyandu , Head of PPSDK, and Heads of The Department of Health then processed and analyzed the data.The results showed that most mothers of children under five did not know that the delivery person must be in good health to come to the posyandu . All mothers of toddlers said that they had prepared their masks to come to the posyandu , while the health officers and cadres were prepared by the health office. Almost all mothers said that one person brought their toddlers to the posyandu .It is suggested that the results of this study can be used as input for making a policy regarding the importance of carrying out health protocols at every posyandu visit.